O enfrentamento da revitimização de crianças vítimas de violência sexual: o caso da inquirição judicial de crianças - Santos, Cristiane Andreotti (2010)
This research presents arguments concerning the hearing of children and adolescents who have been victims of, or witnesses to, sexual violence and mistreatment, aiming at non-re-victimization. The proposed law n. 4.126, of 2004, and its replacement, PLC n. 35/2007, currently passing through the national congress, seek to enshrine in law the experience initiated in Porto Alegre, entitled Deposition without Prejudice This proposal has generated heated debate between professionals in the areas of law, the social services and psychology. The research has as its focus the development of these debates, and the different positions of areas, specially concerning psychology and law. It provides a critical overview of documents in the public domain which are of great importance in understanding the background to these debates. It presents an overview of the concept of the child over a period of time, in which it can be seen that this concept is an historical construction, clearly indicating that violence, particularly sexual violence against the child, became a matter of concern to the authorities and society only in the last quarter of the twentieth century. The research traces out the journey the child victim or witness must make under Brazil s present judicial system. It also touches on other studies which contribute to a fuller and deeper understanding of the different levels and processes at which re-victimization occurs. The study also examines the Deposition without Prejudice and it informs of similar experiments in other countries. However, despite the divergencies existing between the areas, related to the form of how the question of the child re-victimization has been tackled, it is possible to identify a common element: the worry about the protection of the child. The research concludes with an acknowledgement that the legal project concerning the investigation of children mentioned as victims of, or witnesses to, sexual violence or mistreatment has not yet been fully discussed. This discussion must lead to implementation of the methodology showed in the proposed Law n. 4.126, with the incorporation, in the debates, of the democratic opinion of all segments interested in the effective protection of the child